Radon gas measurement in deep gold mines - Dodoo-Amoo, David Nii Amoo (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Physics.